SONET/SDH a sourcebook of synchronous networking - Siller, Curtis A.; Shafi, Mansoor (IEEE Press, 1996)
Counter Gain a comprehensive and up-to-date knowledge of SONET/SDH synchronous networking with this edited anthology of new, original contributions and classic, seminal papers from the foremost leaders in the field. Accurate, logically formatted, and complete with excellent diagrams, this book will be invaluable to communication network and switching engineers who want to stay on the cutting edge of this developing technology. It is adopted by virtually all leading global carriers and equipment.